Interdisciplinary approach involving medical colleagues in managing periodontitis patient with type 2 diabetes: a case report / Nur Zety Mohd Noh ... [et al.] - Mohd Noh, Nur Zety; Hafez Hidayat, Mohd Faizal; Ariffin, Farha; Noor, Erni; Hussain Al-Bayaty, Fouad (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Introduction: Diabetes mellitus has been recognized as a systemic risk factor for periodontitis. Success in controlling periodontitis requires interdisciplinary solutions involving medical counterparts. Case report: This case report highlights the importance of a bidirectional communication between medical and periodontal specialist in the management of a 63-year-old Malay lady patient diagnosed with Generalized Periodontitis, Stage IV and Grade C. The outcome of the interdisciplinary approach was both the stabilization of her periodontal conditions and medically, the glycated haemoglobin level. Conclusions: The bidirectional communication between medical and periodontal specialist is as important as managing the patients medically for a holistic treatment approach of an uncontrolled diabetic patient.